Power misses II : cinema, Asian and modern - James, David E., 1945- (John Libbey Publishing Ltd, 2020)
Like David James' earlier collection of essays, Power Misses: Essays Across (Un)Popular Culture (1996), the present volume, Power Misses II: Cinema, Asian and Modern is concerned with popular cultural activity that propose alternatives and opposition to capitalist media. Now with a wider frame of reference, it moves globally from west to east, beginning with films made during the Korean Democracy Movement, and then turning to socialist realism in China and Taiwan, and to Asian American film and poetry in Los Angeles. Several other avant-garde film movements in L.A. created communities resistant to the culture industries centered there, as did elements in the classic New York avant-garde, here instanced in the work of Ken Jacobs and Andy Warhol. The final chapter concerns little-known films about communal agriculture in the Nottinghamshire village of Laxton, the only one where the medieval open-field system never suffered enclosure. This survival of the commons anticipated resistance to the extreme and catastrophic forms of privatization, monetization, and theft of the public commonweal in the advanced form of capitalism we know as neoliberalism.
Keywords: Motion pictures -- East Asia -- History.; Motion picture industry -- East Asia.; Motion pictures -- California -- Los Angeles -- History.; Asian Americans in motion pictures.; Cinéma -- Californie -- Los Angeles -- Histoire.; Américains d'origine asiatique au cinéma.; Asian Americans in motion pictures; Motion picture industry; Motion pictures; California -- Los Angeles; East Asia; Electronic books.; History